Decolonising Forest Geographies: Explorations of Colonial and Post-colonial North-East India - Marak, Sengsilchi Bolwari (2023)
This thesis is a colonial and post-colonial study of forest policies in North-East India (NEI) that constituted Assam during the colonial period and the seven states of NEI in the post-colonial period. Focussed on the policies peculiar to the region during the colonial period, it sought to explore policies during the post-colonial period in relation to timber ban and Forest Rights Act. In doing so, this thesis perceives these policies through decolonial lens. Decolonial in this study refers to the act of the researcher in studying the forest policies and prioritisation the tribal indigenous perspectives on forest and their traditional governance system of land and forests.